A Qualitative Study of Employees’ Motivation Factors on Organization : A Case Studyfrom a Company in Indonesia - Danu Ade Setiawan (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2020)
Due to the vital function of employees in the organizations that lead to both financial and non-financial performance, man-agement must increase the motivation of their employees. Plenty of researches was conducted in the past decades on the topic ofemployees’ motivation to find the factors that affect the employees’ motivation significantly. This paper examined employees’ mo-tivation factors in one of Indonesia’s state-owned company. Through qualitative approaches, in-depth interviews were conducted toeight active employees with a focus on four predetermined motivation factors that are salary, growth opportunity, work-life balance,and reward/recognition. The result found that all the predetermined factors influence the employees’ motivation to perform wellin the company. Furthermore, the findings also discover some conditions required to be improved regarding specific employees’characteristic such as a supervisory level position. In the end, this paper is expected to generate some possible recommendationsfor the organization to maintain and increase employees’ motivation.